Evaluation and study of the effects of inhomogeneous earthquakes on the response of cable-stayed bridges in terms of soil-structure interaction effects - Hamid Reza Ahmadi; Edris Ghorbani (مدل‌سازی پیشرفته در مهندسی عمران, 2024)
In this study, the behavior of long-span cable-stayed bridges with seismic isolators was analyzed under the effects of non-uniform earthquakes and soil-structure interaction. For this purpose, a three-span cable-stayed bridge with a total length of 1060 meters, including a 600-meter main span, 230-meter side spans, and two 120-meter-high towers, was evaluated.The earthquake records used in this study were from the bedrock and near-field region, within a maximum distance of 10 kilometers. For bridges, assuming the same soil type on either side of the piers, seismic wave reception at each pier occurs with a time delay relative to the other pier, which is more pronounced at lower surface wave propagation velocities.According to the computational results, considering the effects of non-uniform excitations and soil-structure interaction leads to a significant increase in the stresses generated within the structure and the displacement at a single point compared to the uniform excitation scenario.